Феномен и фигура Фонтейна не фантастика - Халфин, Р.Э.; Гниловская, Н.Ф.; Халфин, Р.Р. (Кримський науковий центр НАН України і МОН України, 2005)
After many year-long studies of the invention of by A.E. Yunitsky, an engineer
from Gomel (Byelorussia), and the history of gestation of the invention concept, on
February 1, 2001 R.E. Khalfin, while working in the reading room of the Technical
Literature Section of the Crimean Republican I. Franko Library, made a discovery:
the Yunitsky string-rail is not an original invention as it was in fact invented in the 19th
с and was initially named a "rope rail". The periodicals kept in the library stock made
it possible for R.E. Khalfm to get supplemental information about the true historical
roots of the invention which is of huge importance for the future of the our civilization. Після багатьох років вивчення винаходу інженера А.Е. Юницького у відділі технічної літератури Кримської республіканської універсальної наукової бібліотеки ім. І. Франка 1 лютого 2001 року читачем Р.Е. Халфіним зроблено відкриття: рейка-струна (за Юницьким) є винаходом XIX століття та спочатку називалася рейкою-канатом. Завдяки періодичним виданням, що зберігаються у фонді
бібліотеки, було отримано додаткову інформацію про справжні історичні корені
зародження ідеї, що мають велике значення для долі цивілізації.